The outflow of Asian biomass burning carbonaceous aerosol into the upper troposphere and lower stratosphere in spring: radiative effects seen in a global model - P. Chavan; P. Chavan; S. Fadnavis; T. Chakroborty; C. E. Sioris; S. Griessbach; R. Müller (Atmospheric Chemistry and Physics, 2021)
Biomass burning (BB) over Asia is a strong source of carbonaceous aerosols during spring. From ECHAM6–HAMMOZ model simulations and satellite observations, we show that there is an outflow of Asian BB carbonaceous aerosols into the upper troposphere and lower stratosphere (UTLS) (black carbon: 0.1 to 6 ng m−3 and organic carbon: 0.2 to 10 ng m−3) during the spring season. The model simulations show that the greatest transport of BB carbonaceous aerosols into the UTLS occurs from the Indochina and East Asia region by deep convection over the Malay Peninsula and Indonesia. The increase in BB carbonaceous aerosols enhances atmospheric heating by 0.001 to 0.02 K d−1 in the UTLS. The aerosol-induced heating and circulation changes increase the water vapor mixing ratios in the upper troposphere (by 20–80 ppmv) and in the lowermost stratosphere (by 0.02–0.3 ppmv) over the tropics. Once in the lower stratosphere, water vapor is further transported to the South Pole by the lowermost branch of the Brewer–Dobson circulation. These aerosols enhance the in-atmosphere radiative forcing (0.68±0.25 to 5.30±0.37 W m−2), exacerbating atmospheric warming, but produce a cooling effect on climate (top of the atmosphere – TOA: -2.38±0.12<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="caeaf8af2ce072dc5c345052a2eb35eb"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-14371-2021-ie00001.svg" width="64pt" height="10pt" src="acp-21-14371-2021-ie00001.png"/></svg:svg> to -7.08±0.72<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="e3f23f81ec242a1b4557ebdba74004dd"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-14371-2021-ie00002.svg" width="64pt" height="10pt" src="acp-21-14371-2021-ie00002.png"/></svg:svg> W m−2). The model simulations also show that Asian carbonaceous aerosols are transported to the Arctic in the troposphere. The maximum enhancement in aerosol extinction is seen at 400 hPa (by 0.0093 km−1) and associated heating rates at 300 hPa (by 0.032 K d−1) in the Arctic.